EFFECT OF WORK MOTIVATION, WORK ENVIRONMENT, AND COMPETENCE ON EMPLOYEE PERFORMANCE AT BANK JATENG BOYOLALI REGIONAL BRANCH - Nico Yudea; Sutianingsih Sutianingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research aims to analyze the effect of work motivation on employees, work environment, and competence on employee performance at Bank Jateng Boyolali Branch. This research is a quantitative research by analyzing primary data and secondary data. Primary data is data obtained from the results of questionnaires that have been distributed to all respondents. While secondary data is the data obtained from the data that has been at Bank Jateng Boyolali Branch. Population in research this is employee at Bank Jateng Boyolali Branch with the amount of 88 employees. The data obtained were then analyzed by quantitative methods. The results of this study are motivation work, work environment, and competence has positive and significant influence to performance employees at Bank Jateng Boyolali Branch. Other results also show motivation work, environment work and competence by together have positive and significant influence to performance employees at Bank Jateng Boyolali Branch. Keywords : work motivation, work environment, competence, performance